When College Students Feel They Have Chosen the “Wrong Major”: The Effect of Holland Interest Congruence on Academic Achievement via Academic Engagement and Self-Regulated Learning - Rosyidi, Hamim; Ananda, Meutia (Indonesian Psychological Research, 2026)
This study aims to examine the relationship between Holland interest congruence and students’ academic achievement through the mediating roles of academic engagement and self-regulated learning. The study employed a quantitative approach using an explanatory cross-sectional design involving 240 undergraduate students. The sampling technique used was proportionate stratified random sampling. Data collection was conducted using the Holland RIASEC instrument, the Utrecht Work Engagement Scale–Student Version (UWES-S), the Motivated Strategies for Learning Questionnaire (MSLQ), and students’ Cumulative Grade Point Average (CGPA) data. Data analysis was performed using path analysis. The results indicate that Holland interest congruence has a significant positive effect on academic engagement and self-regulated learning. Furthermore, academic engagement and self-regulated learning were found to have a significant effect on students’ academic achievement. Additionally, a significant direct effect was found between Holland interest congruence and academic achievement, indicating partial mediation. Bootstrapping results also showed that academic engagement and self-regulated learning significantly mediated the relationship between Holland interest congruence and academic achievement.  These findings highlighted the importance of alignment between career interests and the academic environment in fostering student success in higher education.